De Centros Cívicos a Juntas de Acción Comunal : el cambio de modelo de gestión y participación barrial en Medellín en la segunda mitad del siglo XX (2014)
ABSTRACT: Latin American urbanization in the 20th century involves not only a number of challenges for urban dwellers but also the questioning of their political actions against problems related to basic needs such as housing and the access to basic public services. In Medellin, civic centers were created in 1938 as a political figure in the neighborhoods that had a wide coverage and influence on the people and their relationship with the municipal authorities. However, the appearance of the community action associations in 1959, under international precepts and the National Front leadership, establishes a confrontation in some areas of the city and restructures the way of communication between civil society and the State. From a social history approach, this article describes the hard transition from civic centers to community action groups, the position of the authorities, the pro-community speech, its impact on neighborhoods and its importance in shaping the city.